Diffusion coefficients of carbon dioxide in eight hydrocarbon liquids at temperatures between (298.15 and 423.15) K at pressures up to 69 MPa - Cadogan,SP; Mistry,B; Wong,Y; Maitland,GC; Trusler,JPM (Journal of Chemical and Engineering Data, 2016)
We report experimental measurements of the mutual diffusion coefficients in binary systems comprising CO2 + liquid hydrocarbon measured at temperatures between (298.15 and 423.15) K and at pressures up to 69 MPa. The hydrocarbons studied were the six normal alkanes hexane, heptane, octane, decane, dodecane and hexadecane, one branched alkane, 2,6,10,15,19,23-hexamethyltetracosane (squalane), and methylbenzene (toluene). The measurements were performed by the Taylor dispersion method at effectively infinite dilution of CO2 in the alkane, and the results have a typical standard relative uncertainty of 2.6%. Pressure was found to have a major impact, reducing the diffusion coefficient at a given temperature by up to 55% over the range of pressures investigated. A correlation based on the Stokes–Einstein model was investigated in which the effective hydrodynamic radius of CO2 was approximated by a linear function of the reduced molar volume of the solvent. This represented the data for the normal alkanes only with an average absolute relative deviation (AAD) of 5%. A new universal correlation, based on the rough-hard-sphere theory, was also developed which was able to correlate all the experimental data as a function of reduced molar volume with an AAD of 2.5%.